2019
DOI: 10.1002/slct.201900401
|View full text |Cite
|
Sign up to set email alerts
|

Rice Husk Lignin‐Derived Porous Carbon Anode Material for Lithium‐Ion Batteries

Abstract: Lignin carbonaceous is extracted from alkali-treated rice husk waste liquid through an acid precipitation process, and used as carbon source to prepare porous carbon in one-step and twostep methods with zinc chloride as activator at different temperatures. Then the obtained rice husk lignin-derived porous carbon has been used as anode materials for the lithium-ion batteries. After comparison, the material obtained by calcination at 500°C (one-step method) has displayed excellent cycle stability and high cycle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 37 publications
4
28
0
Order By: Relevance
“…With increasing number of cycles, the signals shift to lower potentials (to around 0.05 V after 100 cycles) and the current increases. In former studies, the same trend was observed [21,23] and explained by the wetting of the anode and possible structural changes during charge and discharge processes. [23,29,46] In the first cathodic scan, there is a broad reduction signal at around 0.75 V, which can be associated with electrolyte decomposition and subsequent SEI formation.…”
Section: Half-cell Testssupporting
confidence: 71%
See 4 more Smart Citations
“…With increasing number of cycles, the signals shift to lower potentials (to around 0.05 V after 100 cycles) and the current increases. In former studies, the same trend was observed [21,23] and explained by the wetting of the anode and possible structural changes during charge and discharge processes. [23,29,46] In the first cathodic scan, there is a broad reduction signal at around 0.75 V, which can be associated with electrolyte decomposition and subsequent SEI formation.…”
Section: Half-cell Testssupporting
confidence: 71%
“…At low potentials and cathodic current, lithium ions are reversibly incorporated into the hard carbon. On the anodic scan, there is a corresponding oxidation peak at around 0.2 V, suggesting reversible deintercalation of lithium ions from the hard carbon matrix [21] . With increasing number of cycles, the signals shift to lower potentials (to around 0.05 V after 100 cycles) and the current increases.…”
Section: Half-cell Testsmentioning
confidence: 99%
See 3 more Smart Citations